Strobilurins Influence Morphological Characters And Yield In Chilli (Capsicum Annum L.) (Applied Biological Research, 2016)
The present study was aimed to assess the influence of strobilurin  fungicides on non-fungicidal physiological characters viz.,root length,  plant height, number of branches, leaf area and total dry matter  accumulation in chilli (Capsicum annum). The experiment was laid out  in a randomized block design and comprised of seven treatments of  various concentrations of strobulin fungicides trifloxystrobin and  tebuconazole. The plant height was significantly reduced in all the  strobilurin fungicidal treatments as compared to the untreated control.  Pyraclostrobin in combination with metiram @ 1500 g ha-1 reduced  plant height by 12% over untreated control. The application of  trifloxystrobin + tebuconazole @ 400 g ha-1 gave longer roots, more  number of branches and higher total dry matter accumulation. Further,  it gave maximum green chilli yield (20.44 t ha-1) with 13% increase over  untreated control (15.26 t ha-1).
Keywords: Chilli; dry matter production; leaf area; plant height; root length; strobilurins; yield